2023
DOI: 10.1186/s41239-022-00372-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of artificial intelligence performance prediction and learning analytics to improve student learning in online engineering course

Abstract: As a cutting-edge field of artificial intelligence in education (AIEd) that depends on advanced computing technologies, AI performance prediction model is widely used to identify at-risk students that tend to fail, establish student-centered learning pathways, and optimize instructional design and development. A majority of the existing AI prediction models focus on the development and optimization of the accuracy of AI algorithms rather than applying AI models to provide student with in-time and continuous fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 50 publications
(72 reference statements)
0
32
0
1
Order By: Relevance
“…According to this research, mental load and mental effort are positively correlated and enhance student performance. In addition, Wu (2018) and Yang et al (2023) demonstrated that gamification can facilitate students' comprehension of the material presented on learning platforms and reduce their cognitive load by enhancing playful interactions and increasing engagement. Therefore, based on the findings, this study aims to examine the effect of TTF on cognitive load based on mental load, mental effort, and learning performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to this research, mental load and mental effort are positively correlated and enhance student performance. In addition, Wu (2018) and Yang et al (2023) demonstrated that gamification can facilitate students' comprehension of the material presented on learning platforms and reduce their cognitive load by enhancing playful interactions and increasing engagement. Therefore, based on the findings, this study aims to examine the effect of TTF on cognitive load based on mental load, mental effort, and learning performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, different learning analytics approaches reveals different aspects and yields different outcomes (Nistor & Hernández-García, 2018). However, previous studies put emphasis on examining the impact of the learning analytics approach on one dependent variable, such as knowledge building (Yang et al, 2022), group performance (Ouyang et al, 2023), socially shared regulation (Nguyen et al, 2023), behavioural engagement (Yang & Ogata, 2023), and cognitive load (Larmuseau et al, 2020).…”
Section: Learning Analyticsmentioning
confidence: 99%
“…However, not all students can self‐regulate their learning (Kim, Yu, et al, 2023; Larsen et al, 2012). Given the status quo, faculty members wish to identify such students to give them feedback and encourage them to successfully finish their courses (Cohen, 2017; Ouyang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%